Analisis Kelayakan Finansial dan Strategi Pengembangan Teh Gaharu di Kabupaten Bangka Tengah (Studi Kasus: Teh Gaharu “Aqilla” Gapoktan Alam Jaya Lestari) - Eni Karsiningsih (AGRARIS: Journal of Agribusiness and Rural Development Research, 2016)
This study aims to analyze feasibility of agarwood tea business, to describe marketing strategies of agarwood tea, and to analyze the business development strategy of agarwood tea "Aqilla" Gapoktan Alam Jaya Lestari in Lubuk Pabrik Village, Central Bangka Regency. The method used was a case study. Research shows that agarwood tea business conducted by Gapoktan Alam Jaya Lestari is feasible with a value of NPV Rp. 585,122,261; Net B/C worth 3.6, and IRR worth 40.73%, and the payback period for 4 years and 11 months 8 days. Market penetration strategy used by Gapoktan Alam Jaya Lestari is slow penetration strategy. Agarwood Tea business development strategies that should be done is an aggressive strategy (Growth Oriented Strategy) by improving service, expanding the marketing network, improving the quality and quantity of agarwood tea, adding a variety of flavors, obtaining additional capital, and receiving guidance and assistance from the local government.